Legal Capacity of Regional Organizations in Indonesian Maritime Modernization: A Momentum and Strength - Birahayu, Dita (Fakultas Hukum Universitas Hang Tuah, 2023)
This paper aims to examine the influences of international cooperation between member states of regional organizations in Indonesia's maritime modernization and dispute resolutions of regional international organizations for international violations. This research uses normative juridical research with a statutory approach and a conceptual approach. The results of the discussion show that sea power is the most important element for the progress and glory of a country, which if the sea power is empowered, it will improve the welfare and security of a country. On the other hand, if this sea power is ignored, it will result in losses to a country or even bring down the country. State power can be represented in state membership in international organizations based on the legal capacity of the organization to achieve the objectives of state interests that cover a very broad range of life. Indonesia's active role in international maritime organizations is a momentum and maritime strength in order to support the progress of Indonesia's maritime modernization as stipulated in Presidential Regulation Number 30 of 2019 and dispute resolution between members of the organization based on article 12 Draft Articles on the Responsibility of International Organizations (DARIO).